In Vitro and In Vivo Activities of Ruthenium(II) Phosphine/Diimine/Picolinate Complexes (SCAR) against Mycobacterium tuberculosis - Pavan, Fernando Rogério [UNESP]; Poelhsitz, Gustavo V.; da Cunha, Lucas V. P.; Barbosa, Marilia I. F.; Leite, Sergio R. A. [UNESP]; Batista, Alzir A.; Cho, Sang H.; Franzblau, Scott G.; de Camargo, Mariana S. [UNESP]; Resende, Flávia A. [UNESP]; Varanda, Eliana Aparecida [UNESP]; Leite, Clarice Queico Fujimura [UNESP] (Public Library of Science (PLoS), 2013)
Rifampicin, discovered more than 50 years ago, represents the last novel class of antibiotics introduced for the first-line treatment of tuberculosis. Drugs in this class form part of a 6-month regimen that is ineffective against MDR and XDR TB, and incompatible with many antiretroviral drugs. Investments in R&D strategies have increased substantially in the last decades. However, the number of new drugs approved by drug regulatory agencies worldwide does not increase correspondingly. Ruthenium complexes (SCAR) have been tested in our laboratory and showed promising activity against Mycobacterium tuberculosis. These complexes showed up to 150 times higher activity against MTB than its organic molecule without the metal (free ligand), with low cytotoxicity and high selectivity. In this study, promising results inspired us to seek a better understanding of the biological activity of these complexes. The in vitro biological results obtained with the SCAR compounds were extremely promising, comparable to or better than those for first-line drugs and drugs in development. Moreover, SCAR 1 and 4, which presented low acute toxicity, were assessed by Ames test, and results demonstrated absence of mutagenicity. © 2013 Pavan et al.
Keywords: ethambutol; imine; isoniazid; kanamycin; moxifloxacin; phosphine; picolinic acid; rifampicin; ruthenium complex; streptomycin; acute toxicity; Ames test; animal experiment; animal tissue; antibacterial activity; antibiotic resistance; concentration response; controlled study; drug cytotoxicity; drug effect; drug structure; female; growth inhibition; in vitro study; in vivo study; LD 50; minimum inhibitory concentration; mouse; mutagenicity; Mycobacterium tuberculosis; nonhuman